SIMULATION MODEL OF TRAIN MOVEMENT IN SMALL-RADIUS CURVES - Krec, S.; Janjanin, S.; Stipetic, A. (Science and Transport Progress, 2004)
on the curved sections of track movement of trains as defined in the transverse vibrations of the system "train - path." The simulation model of the system is made in MATLAB language. In tight curves when driving at maximum permitted speed system works under extreme conditions, causing high stress in a carriage and in the train path. Moreover, the system operates with the limit from the viewpoint of safety. The need to quantify the wear of the railway track and trains, assess safety and comfort is particularly relevant at the present time in connection with the commissioning of tilting train, for which the transverse vibrations of the train is very significant. The simulation model also includes the ability to prepare for the measurements and experimental studies, because it allows you to get accurate results, which are expected during sea trials in normal and extreme conditions, leading to time and cost savings.